Conceptualization and Topology Optimization of Ampheel: An Integration of Rolling Wheel and Turtle-Inspired Mechanism for Amphibious Mobile Robot - Mehta, Vishal; Chauhan, Mihir (International Journal of Robotics and Control Systems, 2024)
The primary distinguishing feature of mobile robots is the ability to traverse various environments, setting them apart in the realm of robotics. The mobility of a robot hinges primarily on its locomotion mechanism, which dictates how it moves. The existing unimodal mobile robots are limited to work within the environment for which they are designed for and hence lack a scope to adapt the change in the terrain especially when they put to work in a mixed environment like land and water. Many applications like land and underwater search/rescue, shore infrastructure inspection, coastal area defence and security, offshore energy harvesting, space exploration, etc. demand a mobile robot that can traverse in both terrestrial and aquatic environments with the help of dual or multimodal locomotion mechanism, something like an amphibious animal. Most of the available amphibious robotic solutions have different appendages for both the environment, need human intervention to changeover the mechanism for transition, require different driving system for land and water locomotion and have fragile structures that limit the manoeuvrability. The proposed conceptual design called “Ampheel” is a novel amphibious locomotion mechanism inspired by the biomechanics of freshwater turtles. Ampheel incorporates a rigid wheel, enabling the robot to move on land, integrating soft actuators within it which emulate the turtle's leg-like extensions and enable the aquatic locomotion. Unlike the existing amphibious robots, the Ampheel utilizes the rotational motion of itself as a common driving system for both the environments. This reduces the need of multiple driving systems and also simplifies the control system. Ampheel is designed for safe travelling on land considering the maximum payload of robot as 20 kg including self-weight. Topology optimization of Ampheel is also carried out using ANSYS software for reduction of weight. Additionally, a unique interfacing shaft is designed that transmits the required torque to Ampheel for rotation and also channelise the compressed air to soft pneumatic actuators for inflation during rotation of Ampheel in aquatic setting. The fabricated Ampheel assembly is experimentally checked for failure under the applicable loading condition and found safe.